2021
DOI: 10.24815/siele.v8i2.17694
|View full text |Cite
|
Sign up to set email alerts
|

Strategies employed by EFL doctoral candidates in dissertation writing completion

Abstract: This research study aimed at revealing the strategies employed by successful English as a Foreign Language (EFL) doctoral candidates in accomplishing their dissertation writing and their perspectives in association with the stages of research report writing.  This is a narrative qualitative inquiry, and the data were collected through an in-depth interview with ten successful EFL fresh graduates who had completed their dissertation writing within six and seven semesters. Using a retrospective technique, the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Cognitive strategy is the best or highest category for unsuccessful students. Marhaban et al (2021) found that within EFL learning context, the unsuccessful learners used compensation strategies significantly more often than their successful counterparts.…”
Section: Discussionmentioning
confidence: 89%
“…Cognitive strategy is the best or highest category for unsuccessful students. Marhaban et al (2021) found that within EFL learning context, the unsuccessful learners used compensation strategies significantly more often than their successful counterparts.…”
Section: Discussionmentioning
confidence: 89%
“…The findings were classified into three stages of writing research articles which include challenges, strategies and digital media use in each stage. The stages are determining research topic and finding the relevant references, collecting and analyzing data, and writing each section of the article (Marhaban et al, 2021). The findings show the challenges faced by EFL postgraduate students while conducting research article writing are the lack of language proficiency, the difficulty in discovering the relevant respondents and references, time management, and creating the instruments of data collecting.…”
Section: Resultsmentioning
confidence: 97%
“…Affective strategy is not academic in nature, but it is a critical aspect in writing papers in English because it is related to motivation and emotion management, which help students write successfully. Social strategy refers to a style of social communication in which other people who play a significant part in the completion of research article writing are involved (Marhaban, Mukminatien, Widiati, Sulistyo, Suhastyanang, Puspitasari, & Muslem, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metacognitive skills have also been found to help students complete their final projects (e.g. theses or dissertations), playing a role from the proposal-writing stage to completion (Marhaban et al, 2021). In particular, previous studies have found that the two previously mentioned aspects of metacognition, knowledge of cognition and regulation of cognition, have positive impacts on improving students' writing skills (Cer, 2019).…”
Section: Introductionmentioning
confidence: 99%